Pustakawan masa kini - Ade Uswatun Sitorus (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2016)
Packaging of information is one of development and innovation to improve library services. Definition of packaging information is a process to reprocess the existing information from one form to another better and interesting, The purpose of packaging of information is to bring information resources to users for easy, precise and quick. In this paper described the shapes, stages of the process of packaging activities informasidan also the added value obtained for the library.